Asymmetric-Slit Method on WiFi Antenna with 2.4 GHz and 5 GHz Frequency - Petrus Kerowe Goran; Eka Setia Nugraha (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2020)
Wireless Fidelity (WiFi) devices are often used to access the internet network, both for working and in information searching. Accessing the internet can be administered anywhere provided that the area is within the WiFi devices range. A WiFi device uses 2.4 GHz and 5 GHz operating frequencies. There were several methods employed in the previous studies so that an antenna design could work in two different frequencies, i.e., winding bowtie method, Sierpinski method, and double-circular method. This paper employed a simple method, the slit method. The objective of this paper is to discover a simple antenna model that works on 2.4 GHz and 5 GHz frequencies. This paper employed a square patch microstrip antenna with a slit method. The dimensions of the designed square patch microstrip antenna were 42.03 mm × 27.13 mm × 0.035 mm. The antenna worked at 2.4 GHz and 5 GHz frequencies. The obtained simulation results after the optimization showed that the square patch microstrip antenna using the slit method acquired a value of S11 (return loss) of -10.15 dB at a frequency of 2.4 GHz and -37.315 dB at a frequency of 5 GHz.